Refining population density estimation from track counts: improving daily travel distance estimates through trailing of large herbivores in the Kalahari, Botswana - Marie-Charlotte Gielen; Alessandro Araldi; Marie Jardeaux; Seitshiro Pule; Senxwai Mosololo; Xee Fire Seganaphohu; Duela Seganaphofu; Tebelelo Gabaikanye; Pogiso Ithuteng; Derek Keeping; Nicolas Schtickzelle (Movement Ecology)
Abstract Background Animal track surveys can enable rapid population monitoring for conservation, contingent on a suitable substrate and highly skilled trackers. The Formozov–Malyshev–Pereleshin (FMP) formula converts track counts along transects into absolute population density estimates, using the species' average daily travel distance estimate ( $$\widehat{\text{M}}$$ M ^ ). Its main limitation lies in accurately estimating $$\widehat{\text{M}}$$ M ^ relevant to the survey’s specific time period and location. If empirical $$\widehat{\text{M}}$$ M ^ from the study region is not available, $$\widehat{\text{M}}$$ M ^ can be estimated allometrically, but less accurately, through body mass- $$\widehat{\text{M}}$$ M ^ scaling rules. This study aims to improve the accuracy of FMP-derived density estimates by refining both empirical and allometric $$\widehat{\text{M}}$$ M ^ estimations. Methods We tested a cost-effective forward trailing technique to collect high-quality empirical $$\widehat{\text{M}}$$ M ^ for large herbivore species with local certified trackers, in Khutse Game Reserve and Central Kalahari Game Reserve, Botswana. Since allometric $$\widehat{\text{M}}$$ M ^ values are underestimated in the Kalahari, we calibrated them using empirical $$\widehat{\text{M}}$$ M ^ from this study and the literature. Finally, we integrated our findings to estimate densities of 11 herbivore species using track surveys and the FMP formula. Results Through trailing, we provided empirical $$\widehat{\text{M}}$$ M ^ for five herbivore species, which previously lacked data for the area, and confirmed the temporal stability of daily travel distance values within the study season. We derived two separate coefficients to directly correct allometric $$\widehat{\text{M}}$$ M ^ for Kalahari species based on their foraging strategies. Based on our interpretation of the animal density estimates obtained via the FPM, we discuss the importance of the accuracy of $$\widehat{\text{M}}$$ M ^ , transect design, and survey effort for population monitoring. Conclusion Our research demonstrates the effectiveness of the forward trailing technique for accurately estimating $$\widehat{\text{M}}$$ M ^ of large herbivores in sandy substrates. It also provides coefficients to directly correct allometric $$\widehat{\text{M}}$$ M ^ for Kalahari species and delivers density estimates for multiple herbivores species across 2800 km2 of protected areas. These new elements strengthen the use of track data for wildlife monitoring in low-density environments, although we encourage further research to assess the need of time-specific $$\widehat{\text{M}}$$ M ^ . We also highlight opportunities to integrate Indigenous knowledge with modern technology in research, fostering collaboration with local communities for mutual benefit.